Realistic simulation of drone micro-Doppler signatures - Bennett, Cameron; Harman, Stephen; Petrunin, Ivan (IEEE, 2022)
This paper presents a novel approach to simulating micro-Doppler signatures caused by drones. The focus of this work is to produce realistic signatures that represent the variation that is observed in live radar measurements. In order to accomplish this, the kinematics and dynamics of a drone flight are modelled to capture the changing rotor rotation rates. The simulation results show realistic variation that is representative of measured drone flights.
Keywords: Unmanned aerial vehicles; Radar detection; Micro-Doppler; Simulation; Staring radar